the answer is NOT.. C. please help .
![the answer is NOT C please help class=](https://us-static.z-dn.net/files/d5e/cfa55e8149dbae0dfe21b9393fafeba6.png)
Answer:
Option B
Step-by-step explanation:
First term of the given arithmetic sequence 'a' = -3
Common difference in each successive term 'd' = -8 - (-3)
d = -5
Explicit formula for an arithmetic sequence will be,
[tex]A_n=a+(n-1)d[/tex]
Here, n = number of term
[tex]A_n[/tex] = nth term of the sequence
[tex]A_n=(-3)+(n-1)(-5)[/tex]
For n = 23,
[tex]A_{23}[/tex] = -3 + (23 - 1)(-5)
= -3 - 110
= -113
Option B is the answer.